Enhanced Flexible Mold Lifetime for Roll‐to‐Roll Scaled‐Up Manufacturing of Adhesive Complex Microstructures (Adv. Mater. 2/2023). Issue 2 (12th January 2023) - Kim, Jae‐Kang; Krishna‐Subbaiah, Nagaraj; Wu, Yingdan; Ko, Jongkuk; Shiva, Anitha; Sitti, Metin
Abstract : Roll‐To‐Roll Manufacturing In article number 2207257, Metin Sitti and co‐workers report a two‐step curing‐based roll‐to‐roll manufacturing process for the improvement of the repeatability and durability of flexible silicone molds patterned with complicated adhesive microstructures against highly adhesive polyurethane acrylates. Using the proposed process, the silicone mold demonstrates high durability up to 1000 cycles without significant degradation of the adhesion performance of the printed microstructures.